E-government challenges in developing countries: development of Iraqi e-government - Totonchi, Ahmed; Ahlan, Abdul Rahman (UiTM Press, 2023)
E-government involves utilizing technology to provide information and deliver governmental services to employees, citizens, and businesses. Developing countries implementing e-government should aim to keep pace with rapid technological advances in order to continuously improve their systems and enhance the services offered to citizens through government portals in an efficient manner requiring minimal time and effort. However, many developing nations, especially most Arabic countries, face numerous challenges in implementing and gaining adoption of e-government initiatives. This paper examines the concept, sectors, and definition of e-government, along with the potential benefits. It then discusses the current status of e-government in Iraq, focusing on the issues and obstacles impacting further development of e-government systems in the country. The goal is to provide an overview of e-government and its applications, while analysing the specific difficulties Iraq faces in advancing its e-government efforts in order to identify strategies to overcome these barriers.